Couples' construction of meaning of an Alzheimer's disease diagnosis: a systemic approach - Daniels, Katherine Jean (Kansas State University, 2008)
Alzheimer's disease (AD) is a chronic illness that has the capacity to impact several domains of a person's life. The purpose of this qualitative study was to explore four particular domains of meaning of an AD diagnosis to gain a systemic understanding of couples' experiences when one spouse had recently been diagnosed with Alzheimer's disease. A social constructionist framework was used in conjunction with the biopsychosocial-spiritual model, to explore the biological, psychological, social, and spiritual factors which inform and possibly influence couples' experiences in relation to an AD diagnosis. The interview guide was constructed using the underlying biopsychosocial-spiritual framework for the purpose of exploring couples' experiences in a systemic manner. Four couples were interviewed in their homes, no more than two months following a formal diagnosis of AD. This particular time frame captured the raw experience couples went through when receiving an AD diagnosis. All interviews were recorded, transcribed, and analyzed according to a modified version of Moustakas' phenomenological method of analysis. A family medicine physician served as the co-interpreter throughout the entire analysis process. Results consisted of unique descriptions for each couple's case and a composite description of the cross-case analysis, highlighting similarities and differences among cases. The biopsychosocial-spiritual model was found to be a significant tool for elliciting a systemic understanding of each couple's experience, and recognizing unique aspects of couples' experiences. Analysis across cases revealed 14 common themes that emerged across the four (five biological, four psychological, four social and two spiritual) domains. Results revealed that of the 14 common emerging themes, five themes were shared by all cases: Recognizing a Problem, Experience of Diagnosis Process, Experience of Symptoms, Social Support, and Social Activities. The overall analysis illustrated many more similarities among biological experiences than any other domain of experience. One case, #3, displayed a particularly unique psychological experience, as well as a significant spiritual foundation. Overall, this study emphasized the importance of using a systemic framework, such as the biopsychosocial-spiritual model, to gain a rich, in-depth understanding of how different couples experience the diagnosis process of AD.
Keywords: Alzheimer's disease; Dementia; Marriage; Aging; Social Constructionism; Biopsychosocial-spiritual model; Gerontology (0351); Health Sciences, Mental Health (0347); Psychology, General (0621)